2019
DOI: 10.1038/s41598-019-44586-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling soil detachment by overland flow for the soil in the Tibet Plateau of China

Abstract: The overland flow erosion is common and became more serious because of the climate warming inducing more runoff in the Tibet Plateau. The purposes of this study were to evaluate the effects of flow rate, slope gradient, shear stress, stream power, unit stream power and unit energy of water-carrying section on the soil detachment capacity for the soil in the Tibet Plateau of China due to the information is limited. To achieve this aim, laboratory experiments were performed under six flow rates (5, 10, 15, 20, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…It is possible that the formation and strength of soil aggregates has more to do with size than with material composition. The wetting behavior of soils is of fundamental importance for soil collapse (47,48), creep and liquefaction in landslides (28,49), and slaking erosion that results from disintegration of aggregates (27,29). Modeling frameworks consider only granular friction, fluid drag, and pore pressure effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the formation and strength of soil aggregates has more to do with size than with material composition. The wetting behavior of soils is of fundamental importance for soil collapse (47,48), creep and liquefaction in landslides (28,49), and slaking erosion that results from disintegration of aggregates (27,29). Modeling frameworks consider only granular friction, fluid drag, and pore pressure effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the natural environment, soil cohesion determines the erosion susceptibility of landscapes, including riverbanks, marshes, hillsides, and agricultural fields (25)(26)(27). Cohesion is an important factor in geotechnical applications (28,29), and a crucial parameter in transport of contaminants and microorganisms in the environment (30,31). Many natural and industrial materials are composed of particles of various size, shape, and surface charge, and are subject to intermittent cycles of wetting and drying.…”
mentioning
confidence: 99%
“…Obviously, soil properties in this experiment proved to be the most important factor that significantly influenced soil detachment capacity, determined by soil types and the number of freeze-thaw cycles. The process of soil detachment in the Qinghai-Tibet plateau was significantly lower than that of other regions of China, which was related to the degree of freeze-thaw and soil properties, but the specific mechanism of the effect was unclear [49].…”
Section: Effect Mechanism Of Freeze-thaw On Soil Detachment Capacitymentioning
confidence: 92%
“…Different from the Loess Plateau, the permafrost in the Qinghai-Tibet Plateau was relatively thick, which required long-term field location monitoring and large scale indoor simulation tests for mutual verification [37]. Li et al [38] found that the erosion resistance of the Qinghai-Tibet Plateau was significantly lower than that of other regions, which was related to the degree of freeze-thaw and soil properties, but the specific influencing mechanism remained unclear.…”
Section: Effect Of Freeze-thaw On Soil Erosion Process and Amountsmentioning
confidence: 99%